High‐Capacity All‐Solid‐State Sodium Metal Battery with Hybrid Polymer Electrolytes. Issue 27 (9th August 2018) - Zheng, Yongwei; Pan, Qiwei; Clites, Mallory; Byles, Bryan W.; Pomerantseva, Ekaterina; Li, Christopher Y.
Abstract: All‐solid‐state sodium metal batteries (SSMBs) are of great interest for their high theoretical capacity, nonflammability, and relatively low cost owing partially to the abundance of sodium recourses. However, it is challenging to fabricate SSMBs because compared with their counterparts, which contain lithium metal, sodium metal is mechanically softer and more reactive toward the electrolyte. Herein, the synthesis and electrochemical properties of newly designed sodium‐containing hybrid network solid polymer electrolytes (SPEs) and their application in SSMBs are reported. The hybrid network is synthesized by controlled crosslinking of octakis(3‐glycidyloxypropyldimethylsiloxy)octasilsesquioxane and amine‐terminated polyethylene glycol in existence with sodium perchlorate (NaClO4 ). Plating and stripping experiments using symmetric cells show prolonged cycle life of the SPEs, >5150 and 3550 h at current density of 0.1 and 0.5 mA cm −2, respectively. The results for the first time show that the SPE|sodium metal interface migrates into the SPE phase upon cycling. SSMBs fabricated with the hybrid SPE sandwiched between sodium metal anode and bilayered δ‐Na x V2 O5 cathode exhibit record‐high specific capacity for solid sodium‐ion batteries of 305 mAh g −1 and excellent Coulombic efficiency. This work demonstrates that the hybrid network SPEs are promising for SSMB applications. Abstract : Sodium batteries : All solid‐state sodium metal batteries using hybrid polymer electrolyte, δ‐Na x V2 O5 cathode and metal sodium anode are successfully fabricated with high initial capacity and improved capacity retention.